The problem of stimulating pedagogical teaching and learning of students in a creative heritage of philosophers of antiquity. - Tkachenko O.G (Kharkov National Pedagogical University, 2011)
Article it is devoted an actual historical and pedagogical problem of pedagogical stimulation of educational and informative activity of pupils. In work development of idea of pedagogical stimulation of educational and informative activity of student's youth in the history of foreign thought is tracked, revealed sources and the contribution of foreign teachers to working out of theoretical questions of an investigated problem is defined.